Influence of Planting Media and Biological Fertilizers on the Growth and Rhizome Production of Red Ginger (Zingiber officinale Rosc. Var. Rubrum) - Hapsoh; Yoseva, Sri; R. Reza Arisma (Jurnal Hortikultura Indonesia, 2022)
This study aims to determine the effect of the interaction between the composition of the planting medium and the frequency of application of biological fertilizers on the growth and production of red ginger plants aged five months. This study used a factorial Completely Randomized Design (CRD) consisting of two factors: the planting medium and the application of biological fertilizers. Based on these two factors, 12 treatment combinations were obtained, each treatment with three replications, so that 36 experimental units were obtained, each experimental unit consisted of two polybags, so that the total number of plants was 72 polybags. Parameters observed included shoot age, plant height, number of leaves, leaf length, leaf width, number of tillers, and fresh and dry weight of rhizomes. The results showed that the interaction between the composition of the growing media and the frequency of application of biological fertilizers increased plant height, number of leaves, number of tillers, fresh weight of rhizomes, and dry weight of red ginger rhizomes five months after planting. The combination of the composition of Inceptisol soil + manure + sand (2:1:1) and the application of biological fertilizers by applying three times gave the best results for the growth and production of red ginger.Keywords: red ginger, Zingiber officinale Rosc. Var. Rubrum, planting medium, bio-fertilizer.